Aesthetic Phenomena as Religion: A Study of Tristan and Isolde in The Birth of Tragedy - Field, James Robertson (My University, 1976)
"It is only as an aesthetic phenomenon that existence and the world are eternally justified." This sentence, repeated twice in The Birth of Tragedy, and standing as it does as the essential purpose and motivation of the book, seems to be an intentional turning about of the Lutheran doctrine of sole fide. Here art appropriates to itself what is essentially a religious function; art is the realm of human activity where experiences are ordered and intensified, and subsequently, where redemption is to be gained. In formulating his ideas on art and on Greek tragedy Nietzsche was influenced by Wagner. It was Wagner's music, above all else, that opened up to Nietzsche new problems for art and religion. The musical dissonance of Tristan opened up to Nietzsche the secret key to Greek tragedy. It was the recognition of the Dionysian origin of tragedy, of its origin out of the spirit of music, that enabled Nietzsche to discover the essence of tragedy free from the conventional aesthetics, which expected tragedy to answer the criterion of the plastic arts, that is, of beauty. The Birth of Tragedy announced to the world, as Nietzsche wrote to Wagner, that "practically nothing remains of traditional theories of 'AEsthetics'." In what follows an interpretation of the religious significance of this new aesthetics will be offered by way of a study of the role of Wagner's Tristan and Isolde in The Birth of Tragedy.
Keywords: aesthetic, religion, birth, tragedy, phenomenon, Greek